Peningkatan Daya Saing Pengrajin Aluminium Masa Pandemi Covid-19 Melalui Pembentukan Paguyuban - Jumaiyah; Hazmi, Faiqul; Syahriar, Alfa; Wahidullah (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
Because the covid pandemic of the 19 financial sector, especially small industries, was threatened with bankruptcy, people’s purchasing power fell due to mass layoffs. To build the resilience of small industries it is important to do. The aim of the community partnership program is to help the aluminum industry in Jepara Regency be sustainable. The service implementation method will be carried out in 2 (two) methods, namely the tutorial or lecture method and the implementation assistance where the dedication partner participates in a smaller program that is receiving, practicing knowledge. While in the second method, service partners will be asked to be active in carrying out the various activities provided. The results of this community partnership program The community gathering group was formed for the first time to raise awareness as a member of the group, Make joint agreements on products, materials and standard prices applied and the organizational structure and community activities. The second partner is able to create a delivery plan flow, prioritize work assignments, make a filing, the third partner is able to manage finances and simple bookkeeping training for micro businesses The four partners are able to do marketing through social media (OSS) on the https://www.oss.go.id/